A Qualitative Analysis of Bystander Intervention Among Heavy-Drinking College Men. (August 2018) - Oesterle, Daniel W.; Orchowski, Lindsay M.; Moreno, Oswaldo; Berkowitz, Alan
This study qualitatively examines how heavy-drinking college men conceptualize bystander intervention. Twelve semi-structured individual interviews were conducted with college men reporting past-month heavy drinking and sexual activity within the past 2 months. NVivo software was used to conduct a thematic analysis. Following the stage model of bystander intervention, men in this sample described situations—predominantly in drinking contexts—when other men made sexual advances toward women who were not interested or who were intoxicated as opportunities for intervention. Men reported relying on women's expression of verbal and nonverbal cues as a sign that a situation was problematic, and warranting intervention. Men reported a desire to protect women from experiencing a sexual assault, or to protect a peer from being accused of rape. Men perceived themselves to be more likely to assume responsibility for intervening when the situation involved someone they knew, especially a female friend. A variety of intervention strategies were also reported. Preliminary support was offered for considering alcohol myopia as a barrier to intervention. The interviews also provided preliminary support for further investigation into the role of alcohol expectancies regarding "liquid courage" and "aggression" as factors that can influence bystander intervention when intoxicated. Implications for future research and the development of tailored sexual assault prevention efforts for heavy-drinking men are discussed.